Intervention in civil wars : effectiveness, legitimacy, and human rights - Redaelli, Chiara (Oxford, UK ; Hart Publishing, an imprint of Bloomsbury Publishing, 2020)
"This book investigates the extent to which traditional international law regulating foreign interventions in internal conflicts has been affected by the human rights paradigm. Since the adoption of the Charter of the United Nations, foreign armed interventions in internal conflicts have turned into a common practice. At first sight, it might seem that state practice has developed in a chaotic fashion, however on closer examination, specific patterns emerge. The book charts these patterns by examining the traditional doctrines of intervention and testing them against state practise. The book has two aims. Firstly, it seeks to clarify the current legal framework regulating interventions in internal conflicts. Secondly, it plots the emergence of new trends and investigates whether they are becoming part of positive international law. By taking this dual focus, it offers the first truly comprehensive examination of foreign interventions in internal conflicts"--
Interventions in internal conflicts in the pre-charter era -- Intervention and use of force in the United Nations era -- Interventions by invitation between legitimacy and effectiveness -- Intervention by invitation and governmental (il)legitimacy : rethinking the traditional approaches -- Interventions in favour of governments committing gross and systematic violations of human rights and humanitarian law -- Legitimacy of rebels in international law -- Use of force by and against legitimate rebels : towards the emergence of a jus ad bellum applicable to internal armed conflicts? -- Interventions in favour of rebels and human rights -- Conclusions.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Intervention (International law).; Civil War; Humanitarian law; Human rights; International law; Electronic books